Designing Risk Control Strategies Using HIRARC-Based Risk Management to Comply Occupational Health and Safety Management System Standards in Manufacturing Activities - Auldy Setia Mahendra; Irwan Iftadi (Teknoin, 2025)
Occupational Health and Safety (OHS) is essential for protecting workers from accidents and work related diseases. At manufacturing area PT. XYZ, OHS issues include no compliance with the Occupational Health and Safety Management System (OHSMS) regulations, lack of hazard identification, risk assessment, and control, and insufficient attention to OHS by operator. This study aims to analyze hazards, assess risks, and design appropriate risk control strategies. Using the HIRARC method, which has been proven effective in previous research. The result show that 40.74% of risks fall into the high category, followed by medium (29.63%), low (22.22%), and extreme (7.41%). Risk control strategies based on the Hierarchy of Control are recommended, including eliminating or reducing hazards by distancing hazardous substances from machine areas, replacing parts with safer alternatives, and switching to CNC machines. Engineering controls, such as ergonomic chair designs for operators and noise reduction, administrative controls like procedure design and OHS training, and the use of personal protective equipment (PPE) are also suggested to minimize risks and ensure compliance with established standards.